2020
DOI: 10.1002/ps.6193
|View full text |Cite
|
Sign up to set email alerts
|

Fragments recombination, design, synthesis, safener activity and CoMFA model of novel substituted dichloroacetylphenyl sulfonamide derivatives

Abstract: BACKGROUND Isoxaflutole (IXF), as a kind of 4‐hydroxyphenylpyruvate dioxygenase (HPPD) inhibitor, has been widely used in many kinds of plants. IXF can cause injury in corn including leaf and stem bleaching, plant height reduction or stunting, and reduced crop stand. Safeners are co‐applied with herbicides to protect crops without compromising weed control efficacy. With the ultimate goal of addressing Zea mays injury caused by IXF, a series of novel substituted dichloroacetylphenyl sulfonamide derivatives was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 63 publications
(102 reference statements)
1
43
0
Order By: Relevance
“…It is a highly selective stem and leaf treatment agent. , However, due to the long-term and widespread use of FE, crops suffer varying degrees of phytotoxicity. The application of FE results in crop yellowing, crop growth inhibition, and even crop death in serious cases. To reduce damage to crops, many methods have been reported that incorporate the scientific management of crop rotation and cultivation and the research and development of new herbicides. , In addition, the use of herbicide safeners is also considered to be an efficient solution. …”
Section: Introductionmentioning
confidence: 99%
“…It is a highly selective stem and leaf treatment agent. , However, due to the long-term and widespread use of FE, crops suffer varying degrees of phytotoxicity. The application of FE results in crop yellowing, crop growth inhibition, and even crop death in serious cases. To reduce damage to crops, many methods have been reported that incorporate the scientific management of crop rotation and cultivation and the research and development of new herbicides. , In addition, the use of herbicide safeners is also considered to be an efficient solution. …”
Section: Introductionmentioning
confidence: 99%
“…All known herbicide safeners contain at least one aromatic ring and five or six heterocyclic rings bearing N and O atoms . Bioisosterism and active group combination are the primary methods of developing novel pesticides. Based on the similarities of their molecular structures, several 1,3-disubstituted imidazolidine or hexahydropyrimidine derivatives were designed and synthesized by bioisosterism and active fragment combination (Scheme ). The parent skeleton heterocyclic 1,3-diazo was obtained by bioisosterism using the commercial safener R-28725 as the lead compound.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these test results, the promising compound IV‐6 was evaluated in the field in 2020 65,66 . The results of the field trials are shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%